The Impact of the Pandemic on the Economic Development about Small and Medium Sized Businesses - ZHAKUPOV, Altynbek; YESSILOV, Assylkhan; YELEMESSOV, Alibek; ISMAILOVA, Nargiz (Theoretical and Practical Research in Economic Fields; Vol 14 No 1 (2023): TPREF, Volume XIV, Issue 1(27), Summer 2023, 2023)
The article substantiates the use of a systems approach to the processes about business model switching in small businesses, as this approach was not previously demanded before the pandemic. In this regard, it is concluded that the study of strategic shifts made by small businesses in different segments of the economy is an important new stage in the development of the systems approach. This paper proposes adapting the matrix approach to distinguish crisis states for small businesses according to the properties of their business models: divergent to crisis; crisis-resistant; adaptive; temporarily limited; externally supported; true bankruptcy. A standardized decision-making procedure for digitalization has been developed, and the challenges that small businesses need to address when choosing a digitalization scenario as the minimum necessary sequence of actions, each element of which is necessary to realize the digital transition, have been identified.